Evaluating a community-based exercise intervention with adults living with HIV: protocol for an interrupted time series study. Issue 10 (20th October 2016) - O'Brien, Kelly K; Bayoumi, Ahmed M; Solomon, Patricia; Tang, Ada; Murzin, Kate; Chan Carusone, Soo; Zobeiry, Mehdi; Nayar, Ayesha; Davis, Aileen M
Abstract : Introduction: Our aim was to evaluate a community-based exercise (CBE) intervention with the goal of reducing disability and enhancing health for community-dwelling people living with HIV (PLWH). Methods and analysis: We will use a mixed-methods implementation science study design, including a prospective longitudinal interrupted time series study, to evaluate a CBE intervention with PLWH in Toronto, Canada. We will recruit PLWH who consider themselves medically stable and safe to participate in exercise. In the baseline phase (0–8 months), participants will be monitored bimonthly. In the intervention phase (8–14 months), participants will take part in a 24-week CBE intervention that includes aerobic, resistance, balance and flexibility exercise at the YMCA 3 times per week, with weekly supervision by a fitness instructor, and monthly educational sessions. In the follow-up phase (14–22 months), participants will be encouraged to continue to engage in unsupervised exercise 3 times per week. Quantitative assessment : We will assess cardiopulmonary fitness, strength, weight, body composition and flexibility outcomes followed by the administration of self-reported questionnaires to assess disability and contextual factor outcomes (coping, mastery, stigma, social support) bimonthly. We will use time series regression analysis to determine the level and trend of outcomes across each phase in relation to the intervention. Qualitative assessment : We will conduct a series of face-to-face interviews with a subsample of participants and recreation providers at initiation, midpoint and completion of the 24-week CBE intervention. We will explore experiences and anticipated benefits with exercise, perceived impact of CBE for PLWH and the strengths and challenges of implementing a CBE intervention. Interviews will be audio recorded and analysed thematically. Ethics and dissemination: Protocol approved by the University of Toronto HIV/AIDS Research Ethics Board. Knowledge translation will occur with stakeholders in the form of presentations and publications in open access peer-reviewed journals. Trial registration number: NCT02794415 ; Pre-results.